Ureteroneocystostomy in primary vesicoureteral reflux: critical retrospective analysis of factors affecting the postoperative urinary tract infection rates - Dogan,Hasan Serkan (2014)
Introduction To determine the parameters affecting the outcome of ureteroneocystostomy (UNC) procedure for vesicoureteral reflux (VUR). Materials and Methods Data of 398 patients who underwent UNC procedure from 2001 to 2012 were analyzed retrospectively. Different UNC techniques were used according to laterality of reflux and ureteral orifice configuration. Effects of several parameters on outcome were examined. Disappearance of reflux on control VCUG or absence of any kind of UTI/symptoms in patients without control VCUG was considered as clinical improvement. Results Mean age at operation was 59.2 ± 39.8 months and follow-up was 25.6 ± 23.3 months. Grade of VUR was 1-2, 3 and 4-5 in 17, 79, 302 patients, respectively. Male to female ratio was 163/235. UNC was performed bilaterally in 235 patients and intravesical approach was used in 373 patients. The frequency of voiding dysfunction, scar on preoperative DMSA, breakthrough infection and previous surgery was 28.4%, 70.7%, 49.3% and 22.4%, respectively. Twelve patients (8.9%) with postoperative contralateral reflux were excluded from the analysis. Overall clinical improvement rate for UNC was 92%. Gender, age at diagnosis and operation, laterality and grade of reflux, mode of presentation, breakthrough infections (BTI) under antibiotic prophylaxis, presence of voiding dysfunction and renal scar, and operation technique did not affect the surgical outcome. However, the clinical improvement rate was lower in patients with a history of previous endoscopic intervention (83.9% vs. 94%). Postoperative UTI rate was 27.2% and factors affecting the occurrence of postoperative UTI were previous failed endoscopic injection on univariate analysis and gender, preoperative BTI, postoperative VUR state, voiding dysfunction on multivariate analysis. Surgery related complication rate was 2% (8/398). These were all low grade complications (blood transfusion in 1, hematoma under incision in 3 and prolonged hospitalization secondary to UTI in 4 patients). In long term, 12 patients are under nephrologic follow-up because of hypertension in 5, increased serum creatinine in 5, proteinuria in 1 and hematuria in 1 patient and all these patients had preoperative scarred kidneys. Conclusions Despite its invasive nature, UNC has a very high success rate with a negligible percent of complications. In our cohort, the only factor that negatively affected the clinical improvement rate was the history of previous antireflux interventions where the predictive factors for postoperative UTI were previous failed endoscopic injection, female gender, preoperative BTI, persistent VUR and voiding dysfunction.